USERS READINESS TOWARDS MOBILE APPLICATION: A PRELIMINARY FINDINGS - Norlina Mohamed Noor; Shahril Anwar Mahmud; Ima Shanaz Wahidin; Shahrul Ridzuan Arshad, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2018)
The existence of technology, especially in using the mobile application among users in promoting wireless communications has become essential as part of our life. Mobile application has penetrated in various fields including commerce, services, healthcare, marketing, transportation, finance and entertainment. However, the level of acceptance toward this new technology and the features or taxonomy of the application varies depending on the accessibility, users’ behavioral intention and ease of use towards their satisfaction. The study explores the readiness of the users in term of the intention and the features or the taxonomy of the application in assisting the users to use ARUS, a mobile application which has been developed to furnish essential information on the ferry and boat service in two of the most highly travelled route in Southern Sarawak. The questionnaire focusing the readiness of the users in using the application and the features or taxonomy of the application was distributed online through a goggle form by applying a snowball sampling technique through WhatsApp groups. The results positively revealed that the respondents are ready to use the application and also agreed that the ease of use features or taxonomy of the application can influence them to engage themselves in using the application. In addition, they also agree that the availability of the application would assist them in planning their journey more efficiently. Further research needs to be carried out in order to pursue further investigation on the implementation of the mobile application which is named ARUS.